Study Habits Among Students in Primary Teachers’ Colleges in SouthWestern Uganda - Nuwagaba, James; Mwesigye, Adrian Rwekaza; Karoro, Emmanuel (East African Journal of Education Studies, 2022)
The purpose of the study was to assess the study habits of students in primary teachers’ colleges in South Western Uganda. The research anchored on the Postpositivist philosophy adopted a cohort longitudinal survey research design incorporating correlational techniques. The research employed quantitative methods of data collection in nine government-aided PTCs in South Western Uganda. The sample size was 214 students obtained using simple random sampling from a population of 1192 students in the nine primary teachers’ colleges in South Western Uganda. Data was collected using Palsane and Sharma’s 3-point Likert scale study habits inventory and it was analyzed using SPSS version 20. Research findings revealed that generally, the students in primary teachers’ colleges in South Western Uganda exhibited good study habits in their ability to read and taking of examinations; fair study habits in time management, harnessing physical conditions, note taking, motivation, and memorization; and poor study habits in health and wellness. The conclusion drawn from the findings and other researchers was that students of primary teachers’ colleges in South Western Uganda generally had fair study habits. It was recommended that college administrators and parents should endeavour to organize programs that could assist students in primary teachers’ colleges to acquire good study habits